Exosomal non-coding RNAs: gatekeepers of inflammation in autoimmune disease - Mohamed J. Saadh; Omer Qutaiba B. Allela; Ali Fawzi Al-Hussainy; Lalji Baldaniya; M. M. Rekha; Deepak Nathiya; Parjinder Kaur; Zafar Aminov; Hayder Naji Sameer; Huda Ghassan Hameed; Zainab H. Athab; Mohaned Adil (Journal of Inflammation)
Abstract Autoimmune diseases (AIDs) are marked by systemic inflammation and immune dysregulation, yet current therapies often fail to target their underlying causes. Emerging evidence positions exosomal non-coding RNAs (ncRNAs)—including miRNAs, lncRNAs, and circRNAs—as key regulators of inflammatory pathways, providing critical insights into AID pathogenesis. This review synthesizes recent advances in how these ncRNAs orchestrate immune cell communication, modulate inflammatory mediators, and drive microglial activation in neuroinflammatory AIDs. It evaluates their dual role as disease amplifiers (e.g., miR-155 in lupus, miR-326 in rheumatoid arthritis) and therapeutic targets, emphasizing their potential to reprogram immune responses or deliver anti-inflammatory agents. In this review, we first provide a glimpse into the pathogenesis of autoimmune diseases and delve into the structure and function of exosomes, emphasizing their role in cell-cell communication. We then discuss the regulatory roles of exosomal ncRNAs in immune modulation, detailing their types, functions, and mechanisms of action. Finally, we examine the implications of exosomes and exosomal ncRNAs in the context of autoimmune diseases, with a particular focus on microglial activation and its contribution to neuroinflammation.